2014
DOI: 10.4238/2014.september.12.14
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of 32 microsatellite loci for topmouth culter (Culter alburnus Basilewsky)

Abstract: ABSTRACT. The topmouth culter (Culter alburnus) is an economically important freshwater fish, which is widely distributed throughout large rivers, reservoirs, and lake areas of China. We report here the isolation and characterization of 32 new polymorphic microsatellite loci isolated from genomic DNA in this species enriched by (CA) 12 and (GA) 12 probes. The variability of these microsatellites was tested on 30 individuals cultured. The average allele number was 6.6 per locus, ranging from 3 to 12. The observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…We revealed that Na, Ho and He ranged from 7 to 22, 0.39 to 0.75, and 0.57 to 0.91, respectively. Genetic diversity parameters of microsatellite loci in C. alburnus were slightly higher in our study than previously reported (Liu et al, 2014), but lower than those reported in another study (Fu et al, 2013). It should be noted that the individuals tested and the detection methods were related to the diversity parameters (Liu et al, 2009).…”
Section: Resultscontrasting
confidence: 75%
See 2 more Smart Citations
“…We revealed that Na, Ho and He ranged from 7 to 22, 0.39 to 0.75, and 0.57 to 0.91, respectively. Genetic diversity parameters of microsatellite loci in C. alburnus were slightly higher in our study than previously reported (Liu et al, 2014), but lower than those reported in another study (Fu et al, 2013). It should be noted that the individuals tested and the detection methods were related to the diversity parameters (Liu et al, 2009).…”
Section: Resultscontrasting
confidence: 75%
“…The original sequences released on GenBank database (Liu et al, 2014) were chosen for designing primers. Novel primers were designed for microsatellite loci of differing product sizes.…”
Section: Microsatellite Primer Design and Multiplex Pcrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Culter alburnus (topmouth culter) is an economically valuable freshwater fish species in China [ 9 ]. C. alburnus are widely distributed in various water systems and affiliated lakes in the Yangtze River Basin [ 10 ]. However, insufficient tolerance to hypoxia and AN is an obstacle to the industrialisation of C. alburnus .…”
Section: Introductionmentioning
confidence: 99%
“…To date, research on C. alburnus has mainly focused on nutrition, growth, artificial reproduction, pond culture, and genetic diversity ( Liu et al, 2014 ; Xiao et al, 2014 ; Sun et al, 2015 ). From the perspective of breeding, although C. alburnus has not shown an obvious economic decline phenomenon, molecular studies on the genetic diversity of breeding populations have shown that the genetic diversity of C. alburnus is at a low level ( Qi et al, 2013 ; Qi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%